Characteristics of Si-Y mixed oxide supported nickel catalysts for the reductive amination of ethanol to ethylamines - Jeong, Ye Seul; Woo, Yesol; Park, Myung June; Shin, Chae Ho (Catalysis Today, 2020)
Si-Y mixed oxide synthesis was achieved via Si dissolution from a Pyrex reactor during the synthesis of yttrium hydroxide by the precipitation method at pH 10 and an aging temperature of 100 ℃. The Ni/SY mixed oxide catalysts with 5–25 wt% Ni contents were synthesized using an incipient wetness impregnation method. The characterization of the calcined Ni/SY oxide catalysts was performed using N2-sorption, X-ray diffraction, H2-temperature programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS), and ethanol-TPD. The reaction parameters such as reaction temperature and the partial pressures of ethanol, NH3, and H2 were varied in the reductive amination reaction, and the catalytic activities for the production of monoethylamine, diethylamine, triethylamine, and acetonitrile as main products were compared. The 10 wt% Ni/SY oxide catalyst containing 11 wt% Si showed the maximum activity, and the presence and absence of H2 and NH3 had a great effect on the conversion and selectivities. The stability after 110 h on stream was observed to be 2.5% less than the initial activity. The cause of this deactivation is the formation of nickel carbonitride, as confirmed by XPS and temperature programmed oxidation (TPO) measurements. On the basis of a detailed proposed reaction mechanism, reaction rates were determined, and the kinetic parameters were estimated by fitting the experimental data obtained under a variety of conditions. Our kinetic model showed that the temperature and the partial pressures of ethanol and hydrogen significantly influenced the conversion, whereas the partial pressure of ammonia had little influence because the imine partial pressure rapidly reached saturation.
Keywords: Deactivation; H2 temperature-programmed reduction; Incipient wetness impregnation method; Kinetic modeling; Nickel catalyst; SiO2-Y2O3; Supported nickel catalysts; Temperature programmed oxidation; Amination; Carbonitride; Deactivation; Ethanol; Kinetic model; Nickel catalyst; SiO2-Y2O3